Analisis Kemampuan Membaca Anak Usia Dini Di RA Al-Huda Kecamatan Sawit Seberang - Herlin Syahdina Lubis, Nadia Turrohmah, Nunzairina, Nanda Yuliantika, Della Fadillah Febrianti (Ability: Journal of Education and Social Analysis, 2023)
Associated with the problems that exist in early childhood education who still have difficulty in the early stages of reading early childhood. As a PAUD teacher, of course, you must have a strategy in improving children's reading skills, especially in the early stages of recognizing the letters of the alphabet. Research conducted on students at RA Al-Huda aims to improve the ability of these students to read and recognize letters. To make children good at reading, the most important thing for parents and teachers is to choose media or tools that can help hone their abilities in a fun way and with the right strategy. Cleverness in reading is certainly a very unique skill and plays an important role in the development of science and as a means of communication. Based on the description of the results that have been presented, the following will explain the discussion of each. - Students are able to recognize vowels. Based on the results of the study, it was found that 34% (5 people) of students were able to recognize vowels very well. - Students are able to mention vowels. Based on the results of the study, it was obtained data that 34% (5 people) of students were able to pronounce vowels very well. - Learners are able to sort the letters of the alphabet from A - Z about 75%. - Learners are able to combine two syllables about 20%. 12 - Students are fluent in reading about 10%. - Students are able to distinguish the letter b with d, p with q about 50%.